2016
DOI: 10.21475/ajcs.2016.10.09.p7648
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest application of 1-MCP and ethylene influences fruit softening and quality of ‘Arctic Pride’ nectarine at ambient conditions

Abstract: Fruit softening in nectarine is a limiting factor for their extended postharvest life with best quality. Effects of postharvest exogenous applications of 1-MCP (1 µL L -1 ), ethylene (10 µL L -1 ) or 1-MCP (1 µL L -1 ) followed by ethylene (10 µL L -1 ) for 12 h on 'Arctic Pride' nectarine were investigated for changes in fruit softening and quality during ripening at ambient temperature (20 ± 1 o C; 60-65% RH). Untreated fruit were kept as control and stored at the same conditions i.e. 20 ± 1 o C; 60-65% RH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Such induction could be explained by the fact that 1-MCP shuts down the system of feedback regulation of ethylene biosynthesis pathway by binding to physiological ethylene receptors [36], inhibiting the ethylene binding protein [37] and hence disabling the host to perceived any ethylene quantities already synthetized. Moreover, exogenous ethylene treatment also enhanced ethylene production, in agreement with previous results in both climacteric and non-climacteric systems [35,38], probably through the induction of ACS expression [39] and/or ethylene receptors [40].…”
Section: Discussionsupporting
confidence: 91%
“…Such induction could be explained by the fact that 1-MCP shuts down the system of feedback regulation of ethylene biosynthesis pathway by binding to physiological ethylene receptors [36], inhibiting the ethylene binding protein [37] and hence disabling the host to perceived any ethylene quantities already synthetized. Moreover, exogenous ethylene treatment also enhanced ethylene production, in agreement with previous results in both climacteric and non-climacteric systems [35,38], probably through the induction of ACS expression [39] and/or ethylene receptors [40].…”
Section: Discussionsupporting
confidence: 91%
“…It is well-known that fruit softening enzymes are involved in the reduction of intercellular adhesion and tissue rigidity during fruit ripening [55], and an increase in fruit softening degree is associated with an increase in softening enzyme activity. A similar conclusion was reached in the study of 1-MCP-treated nectarines by Ullah et al [56], which found that untreated nectarine pulp tissues exhibited decreased firmness and intercellular adhesion, while nectarines treated with 1-MCP showed increased chewiness, potentially due to decreased softening activity in the fruit. The substantial impact of 1-MCP treatment on fruit softening can be attributed to its active involvement in reducing ethylene levels within fruits, thereby impeding fruit softening and delaying ripening.…”
Section: Relationship Between Postharvest Grape Fruit Softening and C...supporting
confidence: 82%
“…When mango was treated with 2.0 l/L at 20 o C for 12 h, it preserved the post-harvest quality of the fruit (Kou et al, 2020). The administration of 1.0 l/L of 1-MCP on persimmon for 18 h at 20 o C indicates that fruit softness and ethylene synthesis were postponed (Ullah et al, 2016). Post-harvest treatment with 1-MCP in nectarines reduced ethylene formation and fruit-softening enzyme activity (Grozeff et al, 2017).…”
Section: -Methylcyclopropene (1-mcp)mentioning
confidence: 99%
“…The contents of amino acids and glutathione in blueberry fruit have improved dramatically when 1-MCP is applied (Horvitz and Cantalejo, 2014). There are numerous possibilities for combining 1-MCP with advanced technologies to provide consumers with highquality horticultural produce while lowering post-harvest losses, particularly for perishable fruits (Ullah et al, 2016;Horvitz and Cantalejo, 2014).…”
Section: -Methylcyclopropene (1-mcp)mentioning
confidence: 99%